Rapid Inactivation of Non-Endospore-Forming Bacterial Pathogens by Heat Stabilization is Compatible with Downstream Next-Generation Sequencing. (September 2019) - Schroeder, Max R.; Loparev, Vladimir
Introduction: Heat stabilization treatment preserves the in vivo state of biological samples by rapidly inactivating enzymes that cause degradation of proteins and nucleic acids. Historically, proteomics studies used this technique as an alternative to chemical fixation. More recently, microbiologists discovered that heat stabilization treatment rapidly inactivates pathogens present in tissue samples and preserves deoxyribonucleic acid (DNA) in the tissue. However, these recent studies did not investigate the inactivation of high-density bacterial suspensions and the quality of bacterial DNA. Methods and Results: High-density suspensions of Escherichia coli (>10 9 cfu/mL) were completely inactivated by heat stabilization treatment using the Denator Stabilizor T1 instrument at 72°C and 95°C for 45 seconds. Using the heat stabilization instrument, a panel of 30 species, 20 Gram-negative and 10 non-endospore-forming Gram-positive species, were fully inactivated by treatment (95°C for 45 seconds). DNA was isolated from bacterial suspensions of Gram-negative bacteria, including E. albertii, E. coli, Shigella dysenteriae, and S. flexneri, following inactivation via heat stabilization treatment and without treatment. DNA isolated following heat stabilization treatment was fully compatible with all downstream molecular applications tested, including next-generation sequencing, pulsed-field gel electrophoresis, multiplex polymerase chain reaction (PCR), and real-time PCR. Conclusions and Discussion: Heat stabilization treatment of Gram-negative and non-endospore-forming Gram-positive pathogens completely inactivates high-density bacterial suspensions. This treatment is compatible with downstream DNA molecular assays, including next-generation sequencing, pulsed-field gel electrophoresis, and PCR. Inactivation by heat stabilization is a rapid process that may increase safety by decreasing risks for laboratory-associated infections and risks associated with transportation of infectious materials.